MSME Segmentation in Pekanbaru Based on Local E-Catalog Participation Using K-Means - Rahma Aliya; Inggih Permana; Febi Nur Salisah; Rice Novita; Muhammad Jazman (LKP KARYA PRIMA KURSUS, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy; however, their participation in digital government procurement platforms such as the Local E-Catalog in Pekanbaru City remains relatively low. The lack of comprehensive, data-driven mapping of MSME characteristics has resulted in less targeted development and assistance programs. This study aims to segment MSMEs based on revenue, number of employees, and participation status in the Local E-Catalog to generate business groups that can support more effective development strategies. A data mining approach using the K-Means clustering algorithm was applied and implemented through the Orange Data Mining application. The results indicate that a three-cluster configuration is the most optimal, achieving the highest Silhouette Score of 0.444. Cluster 1 represents micro-scale MSMEs with low business capacity and minimal participation in the Local E-Catalog, Cluster 2 consists of growing MSMEs with moderate business capacity, and Cluster 3 comprises established MSMEs with high business capacity and active participation in the Local E-Catalog. These findings provide empirical evidence to support local governments in formulating more targeted and data-driven policies for accelerating MSME digitalization.